2010
DOI: 10.1007/s11255-010-9720-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of core biopsy fragmentation in prostate cancer

Abstract: Considering the ongoing trend for earlier diagnosis of increasing numbers of younger men with low-risk prostate cancer, this study is original and demonstrates the possibility of core fragmentation, explaining in part over- and under-staging. One core per container and an overall Gleason score and percentage of adenocarcinoma for each container are encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…The number of biopsy cores obtained varied considerably and, in the present study, ranged from 4 to 27. Furthermore, fragmentation of biopsy cores may skew the interpretation of biopsy results, including the number and percentage of biopsy cores positive [24,25]. Biopsy can lead to complications and has been associated with mortality [26], although the causality of this association has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The number of biopsy cores obtained varied considerably and, in the present study, ranged from 4 to 27. Furthermore, fragmentation of biopsy cores may skew the interpretation of biopsy results, including the number and percentage of biopsy cores positive [24,25]. Biopsy can lead to complications and has been associated with mortality [26], although the causality of this association has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Reis et al demonstrated that pathologists often receive more cores than the number sampled by the urologist and suggested that these changes are due to core fragmentation. 39 In their study, biopsies resulted in 21.54 (±3.56) cores, whereas pathologists examined 24.08 (±4.77, p<0.01) cores. Core numbers by all prostate gland areas (such as right and left base, mid-gland, and apex) were statistically different between biopsy and pathological examination reports (p<0.01).…”
Section: Resultsmentioning
confidence: 97%
“…When there was a nodule on digital rectal prostate examination or a hypoechoic area was detected through ultrasound, 02 additional biopsy cores were taken from these sites [14]. …”
Section: Methodsmentioning
confidence: 99%